PEMBENAHAN MANAJEMEN PROGRAM INTRODUCTION TO COLLEGE ENGLISH (ICE) DALAM MENINGKATKAN PARTISIPASI MAHASISWA - Mega Wati (Universitas Negeri Yogyakarta, 2007)
Abstract This action research aims at promoting students’ participation in a class of repeaters so that they can attend classes regularly and be actively involved in the learning process in the classroom through the coordinated actions of the two teachers as a work team. This action research was done in four cycles at the English Language Training Center of Duta Wacana Christian University during the second semester of the 2004/2005 academic year. The participants of the research were the two classes of repeaters at the lowest level of the Introduction to College English (ICE) program (Level 1A) and two other teacher collaborators with whom the researcher taught those classes and did the researcher. Data were collected by means of observation, interview, and document. The data were then analyzed by using the Interactive Analysis Model of Miles and Huberman. The findings show that the increased teacher coordination as a work team through coordinating meetings, Teacher’s Journal and dialogs in teaching learning-strategy, developing students’ sense of achievement, motivating and empowering, and using certain instructional techniques has resulted in an effective synergy to create a productive climate in which the students feel cared for, motivated, and empowered by their two teachers. The extra score from comiling teaching materials is quite motivating for the students and has proven to be helpful for some student to reach the passing score. Keywords: Restructuring programmanagement; promoting teacher coordination;promoting students’ participation